2013
DOI: 10.3346/jkms.2013.28.8.1122
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Cigarette Smoking and Total Mortality Differ Depending on Serum Concentrations of Persistent Organic Pollutants among the Elderly

Abstract: There are substantial variations of relative risks (RR) in smoking-related mortality by country and time. We hypothesized the RRs in smoking-related mortality might differ depending on serum concentrations of persistent organic pollutants (POPs). We evaluated the associations of cigarette smoking with total mortality in 610 elderly (aged ≥ 70 yr) (702 elderly for organochlorine pesticides [OCPs]) after stratification by serum concentration of POPs, in the National Health and Nutrition Examination Survey (NHANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
4
15
0
Order By: Relevance
“…While not statistically significantly in our analyses, the suggestion of greater mortality among overweight and obese individuals with high OC pesticide exposure is opposite than reported previously. [ 41 , 68 ] Conversely, while we did not observe significant effect modification by ACR, our point estimates were often consistent with the prior report of greater mortality among those with high ACR and high OC pesticide exposure [ 69 ] or among current smokers with high OC pesticide exposure [ 70 ]. The suggestion that sex modifies the OC pesticide other-cause mortality association is potentially plausible given potential endocrine-disruption related effects of exposure [ 71 ], but requires further confirmation in other samples.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While not statistically significantly in our analyses, the suggestion of greater mortality among overweight and obese individuals with high OC pesticide exposure is opposite than reported previously. [ 41 , 68 ] Conversely, while we did not observe significant effect modification by ACR, our point estimates were often consistent with the prior report of greater mortality among those with high ACR and high OC pesticide exposure [ 69 ] or among current smokers with high OC pesticide exposure [ 70 ]. The suggestion that sex modifies the OC pesticide other-cause mortality association is potentially plausible given potential endocrine-disruption related effects of exposure [ 71 ], but requires further confirmation in other samples.…”
Section: Discussionsupporting
confidence: 89%
“…This limited our ability to detect small effect and our ability to further investigate the association with more refined cause-specific mortality categories. Similarly, although motivated by evidence of effect modification in other settings [ 34 , 68 70 ], we consider our analyses of effect modification to be exploratory given our small sample. Future work in larger samples will be required to examine the effect of exposure within potentially susceptible sub-populations.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to link POPs contamination with ESRD and death among persons with type 2 diabetes. Previous studies showed early mortality with POPs exposure, particularly due to an increased risk of breast and pancreatic cancers [16, 17, 43].…”
Section: Discussionmentioning
confidence: 99%
“…A study of kidney biopsies in the arctic fox found a wide range of kidney tissue damage associated with exposure [15], but this association has not been studied in humans. POPs are also associated with early mortality in the elderly and in cigarette smokers [1617].…”
mentioning
confidence: 99%
“…In addition, exposure to OCPs in combination with other pollutants, like inorganic toxic elements, may facilitate an additive or synergistic effect [ 15 ]. An interesting study of 702 adults over the age of 70 years, for example, reported significantly higher mortality levels in smokers in the 2nd or 3rd tertile of OCP blood levels but not among smokers in the lowest tertile of exposure [ 16 ].…”
Section: Introductionmentioning
confidence: 99%